Indian Literary Style: The Dominant Characteristics in Poetry in Persian and Ottoman Turkish Languages - Karahalilović, Namir; Ćatović, Alena (Prilozi za orijentalnu filologiju, 2017)
Since the 16th century, when the Indian literary style first found its way to the Persian literature as a result of Iran’s specific cultural and social milieu formed during the Safavids’ dominion, it has also spread its influence over other Oriental-Islamic literatures. Due to its vast geographical expansion in the course of the next three centuries and through the interaction with different traditions in different parts of the world the presence of the Indian literary style in Oriental-Islamic literature acquired some new specific characteristics of which it was deprived at its first appearance. Its traces have been recognised even in the works from the postclassical period Ottoman literature created in the distant west province of Bosnia. This paper analyzes the dominant characteristics of the Indian literary style – such as paradox image, synesthesia, personification and abstraction – in the poetry written in Persian and Ottoman Turkish languages with a special review of Bosniac literary heritage in these two languages.